Mitologi Buyut Cili Kepercayaan dan Habituasi Transendental Suku Using, Banyuwangi - jainudin jainudin (Religió: Jurnal Studi Agama-agama, 2019)
The history of the mythology of Using Tribe in Banyuwangi has been rooted within the ancestral beliefs of Hinduism and Buddhism. Using Tribe used to do a pilgrimage (ziarah) to what so called Petilasan Buyut Cili which is believed as ground-breaker of the construction of Using. This research aims to describe history of Petilasan Buyut Cili, cultural changes of the ancestral faith, and transcendental habituation. Using phenomenological approach, this research attempts to elucidate that social belief could create a basically well-balanced connection between human and God. This research found that (1) the growth of the belief of Using Tribe has been influenced by Department of Tourism which established Kemiren Village as a traditional and cultural village; (2) urbanization changes religious patterns of Using Tribe; and (3) the tribe has been transformed to be a religious-based tourist destination. The tribe practiced annual religious rites which are conserved simultaneously to become a transcendental habituation for the people of Desa Kemiren.